Central obesity in Yemeni children: A population-based cross-sectional study - Bamoshmoosh, Mohamed; Massetti, Luciano; Aklan, Hameed; Al-Karewany, Mahdi; Al Goshae, Husni; Modesti, Pietro Amedeo (Baishideng Publishing Group Inc., 2013)
AIM: To establish percentile curves and to explore prevalence and correlates of central obesity among Yemeni children in a population based cross-sectional study. METHODS: A representative sample of 3114 Yemeni children (1564 boys, 1550 girls) aged 6-19 years participating in the HYpertension and Diabetes in Yemen study was studied. Data collection was conducted at home by survey teams composed of two investigators of both genders. Study questionnaire included questions about demographics, lifestyle, and medical history. Anthropometric measurements included body weight, height, waist circumference (WC) and hip circumferences. Waist to hip ratio (WHR) and waist-to-height ratio (WHtR) were then calculated. Age and gender specific smoothed percentiles of WC, WHR, and WHtR were obtained using lambda-mu-sigma parameters (LMS method). The independent predictors of central obesity defined as (1) WC percentile ? 90th; (2) WHtR ? 0.5; or (3) WC percentile ? 90th and WHtR ? 0.5, were identified at multivariate logistic regression analysis adjusted for age, gender, urban/rural location, years of school education, sedentary/active life-style. RESULTS: Percentile curves for WC, WHR and WHtR are presented. Average WC increased with age for both genders. Boys had a higher WC than girls until early adolescence and thereafter girls had higher values than boys. WHR decreased both in boys and girls until early adolescence. Thereafter while in boys it plateaued in girls it continued to decrease. Mean WHtR decreased until early adolescence with no gender related differences and thereafter increased more in girls than in boys towards adult age. Prevalence of central obesity largely varied according to the definition used which was 10.9% for WC ? 90th percentile, 18.3% for WHtR ? 0.5, and 8.6% when fulfilling both criteria. At adjusted logistic regression WC ? 90th percentiles and WHtR ? 0.5 were less prevalent in rural than in urban areas (OR = 0.52, 95%CI: 0.41-0.67 and 0.66, 0.54-0.79 respectively), being more prevalent in children with sedentary lifestyle rather than an active one (1.52, 95%CI: 1.17-1.98 and 1.42, 95%CI: 1.14-1.75, respectively). CONCLUSION: Yemeni children central obesity indices percentile curves are presented. Central obesity prevalence varied according to the definition used and was more prevalent in urban sedentary subjects. Bamoshmoosh M, Massetti L, Aklan H, Al-Karewany M, Goshae HA, Modesti PA.Central obesity in Yemeni children: A population based cross-sectional study.World J Cardiol2013;5(8): 295-304 [PMID: 24009819 DOI: 10.4330/wjc.v5.i8.295]